2013
DOI: 10.1039/c3ta11345k
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electrochemical properties of multiple metal oxide nanoparticles as cathodes of lithium batteries

Abstract: Multiple metal oxide nanoparticles, which are the solid solutions of various kinds of divalent and trivalent metal ion oxides containing a certain amount of cation vacancy, with a uniform particle size less than 20 nm and huge surface area were synthesized by the calcination of layered double hydroxide (LDH) precursors, and their structures were analyzed using XRD and EXAFS. The electrochemical properties of these metal oxide nanoparticles as the cathode electrodes of Li batteries were also investigated by cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…One of the key factors is vacancies to compensate the excess charge of the higher valent vanadium ions and to keep the charge neutrality. They also confirmed Li + ions are inserted into cation vacancies in the Ni-V oxide by using XRD patterns and EXAFS analyses [3]. Moreover, Koo et al showed that a high concentration of cation vacancies in iron-oxide 25 nanoparticles leads a high capacity of about 132 mAhg −1 at a high voltage of 2.5 V without fading during more than 500 charge-discharge cycles [5].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…One of the key factors is vacancies to compensate the excess charge of the higher valent vanadium ions and to keep the charge neutrality. They also confirmed Li + ions are inserted into cation vacancies in the Ni-V oxide by using XRD patterns and EXAFS analyses [3]. Moreover, Koo et al showed that a high concentration of cation vacancies in iron-oxide 25 nanoparticles leads a high capacity of about 132 mAhg −1 at a high voltage of 2.5 V without fading during more than 500 charge-discharge cycles [5].…”
Section: Introductionmentioning
confidence: 89%
“…All the chemicals used in this study were purchased from Kishida chemical (GR grade). A precursor of NiAllayer double hydroxides (LDHs) was synthesized by a coprecipitation method using Ni(NO 3 ) 2 •6H 2 O and Al(NO 3 ) 3 as starting materials [3]. An aqueous solution containing 1M NaOH and 0.1 M Na 2 CO 3 was added dropwise into the aqueous solution containing Ni:Al with a ratio of 2:1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Typically,t he energy density of supercapacitors composed of porous activated carbon electrodes in aqueouselectrolyte is about 4-5 Wh kg À1 , [4] which is about one fifth that of lead acid batteries (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Wh kg À1 ) and much lower than that of lithium ion batteries ( % 180 Wh kg À1 ). [7] Even though those organic electrolytesh ave ah ighero perating voltage than aqueous electrolytes, carefula nd expensive thermal controlsa re required for the necessary security requirementsc aused by the flammability and the high vapor pressure of the electrolytes. [7] Even though those organic electrolytesh ave ah ighero perating voltage than aqueous electrolytes, carefula nd expensive thermal controlsa re required for the necessary security requirementsc aused by the flammability and the high vapor pressure of the electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] The carbon-based supercapacitors employ aprotics olvents as the electrolyte solutions,t ypicallya cetonitrile (ACN) or carbonate-based solvents such as propylene carbonate, ethylene carbonate. [7] Even though those organic electrolytesh ave ah ighero perating voltage than aqueous electrolytes, carefula nd expensive thermal controlsa re required for the necessary security requirementsc aused by the flammability and the high vapor pressure of the electrolytes. [8] Thus,i ti s essential to construct the suitable electrode materials and optimize the matched electrolytes to produce the efficient and secure supercapacitors with balanced powera nd energy densities.…”
Section: Introductionmentioning
confidence: 99%